Analisis Kebijakan Program Ekoteologi UIN Sulthan Thaha Saifuddin Jambi: Tantangan Kurikulum dan Sinergi - Risye Martarika (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article is motivated by the unsuccessful implementation of the Ministry of Religious Affairs' ecotheology priority program at UIN Sulthan Thaha Saifuddin Jambi. A gap exists between the program's ideal goal of producing relevant graduates and the reality on the ground, where curriculum implementation has not been effectively integrated with the real needs of the local community and industry, and weak synergy between stakeholders. The methodology of this paper uses a qualitative approach with a descriptive analysis approach, case study and Urgency, Seriousness, Growth (USG) analysis and William N. Dunn's theory. The results of the paper indicate that